1998
DOI: 10.1038/sj.onc.1201705
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant PML adenovirus suppresses growth and tumorigenicity of human breast cancer cells by inducing G1 cell cycle arrest and apoptosis

Abstract: Our previous studies demonstrated that the promyelocytic leukemia gene, PML which involved in the 15;17 translocation in acute promyelocytic leukemia (APL) is a growth and transformation suppressor. In this study, recombinant PML adenovirus, Ad-PML was constructed and used to infect human breast cancer cells in vitro and in vivo, the anti-oncogenic function of PML and its mechanism of growth suppressing e ect in breast cancer cells were examined. We showed that Ad-PML e ectively infected the MCF-7 and SK-BR-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 29 publications
(43 reference statements)
11
86
0
Order By: Relevance
“…Blots were probed with the actin antibody to indicate the quantity of protein loaded into each lane. Consistent with these ®ndings, previous reports indicated that cyclin D1 protein levels were reduced by PML overexpression in breast cancer cells but provided no mechanism for this observation (Le et al, 1998). Our data indicate that this suppression is mediated at least in part through eIF-4E.…”
Section: Pml Overexpression Alters Production Of Cyclin D1 Proteinsupporting
confidence: 90%
“…Blots were probed with the actin antibody to indicate the quantity of protein loaded into each lane. Consistent with these ®ndings, previous reports indicated that cyclin D1 protein levels were reduced by PML overexpression in breast cancer cells but provided no mechanism for this observation (Le et al, 1998). Our data indicate that this suppression is mediated at least in part through eIF-4E.…”
Section: Pml Overexpression Alters Production Of Cyclin D1 Proteinsupporting
confidence: 90%
“…All mice were maintained under specific pathogen-free conditions and given sterile food and water. A 17b-estradiol pellet (Innovative Research of America, Sarasota, FL, USA) was implanted as described previously (Le et al, 1998). Once the tumors became palpable (mean size of 0.2-0.3 mm 3 at day 12 after injection), mice were divided into two groups and treated i.p.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…Tumor sizes and body weights were measured twice a week by the same observer. The tumor volume in mm 3 was calculated as described previously (Le et al, 1998). Experiments with nude mice were repeated three times with similar results.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…14 -17 For example, in contrast to AdN5, cells containing wt p53 are less sensitive to Adp53 than cells lacking wt p53. 18 Furthermore, Adp53 and AdPML infection induces G 1 cell cycle arrest and subsequent apoptosis, 15,19 whereas AdE2F-1 infection induces premature entry into S phase. 20 In contrast, AdN5 causes a G 2 /M cell cycle arrest followed by apoptosis (J. Doostzadeh-Cizeron, unpublished observations).…”
Section: Yin Hung and Goodrich: N5 Adenovirus Induces Apoptosis In mentioning
confidence: 99%